Direct visualization of photo-induced disulfide through oxidative coupling of para-aminothiophenol. Issue 34 (31st March 2021) - He, Wei; Xia, Chang; Gao, Peng Fei; Zhou, Jun; Li, Yuan Fang; Huang, Cheng Zhi
Abstract : Catalyst-free photooxidation dimerization of para -aminothiophenol ( p -ATP) to 4-aminophenyl disulfide (APDS) in water was identified and monitored in real time by dark-field microscopy through the formation of organic nanoparticles. Abstract : Chemical transformations under visible irradiation are interesting in green preparation. Herein, a photo-oxidative coupling reaction of para -aminothiophenol ( p -ATP) dimerizing to 4-aminophenyl disulfide (APDS) rather than 4, 4′-dimercaptoazobenzene (DMAB) was achieved in water by visible light irradiation, producing monodispersed organic nanoparticles in situ with strong light scattering visualized by the dark-field microscopy (DFM) imaging technique, owing to the formation of disulfide.